El estilo de liderazgo autocrático del gerente y la motivación laboral en la institución educativa de acción conjunta "santísimo sacramento" del distrito de La Esperanza, provincia de Trujillo, la libertad - 2015 - Castillo Sevilla, Roxana Milagros (2016)
This research was aimed to determine the relationship between autocratic leadership style of the manager and work motivation in Educational Institution Joint Action "Blessed Sacrament" District of La Esperanza, Province of Trujillo, La Libertad – 2014 The population consisted of all workers in the educational community among principals, administrators, teachers and assistants initial, primary and secondary levels; the sample consisted of the entire population: 36 people. A non-cross experimental design was used in the correlational method, based on application of scientifically validated tools, Campoverde Survey dimensioned in four areas: employee relations, conflict management, task structure, and leader's power; Motivation Scale also Steers and Braunstein dimensioned in three areas: level of achievement, level of power. and membership level. According to surveys conducted leadership style was characterized as autocratic, regular acceptance level as the level of work motivation. Regarding the analysis linked to the hypothesis worked with Pearson coefficient to determine if there is significant relationship between the variables; to obtain a p-value = -0.080 less than 0.05 the null hypothesis is rejected, accepting that there is a relationship between autocratic leadership style of the manager and work motivation of the Educational Institution.